The Informational Effects of Tightening Oil and Gas Disclosure Rules - Badia, Marc; Duro, Miguel; Jorgensen, Bjorn N.; Ormazabal, Gaizka; Christensen, Hans B. (Contemporary Accounting Research, 2020)
ABSTRACT We exploit two regulatory shocks to examine the informational effects of tightening preexisting mandatory disclosure rules. Canadian National Instrument 51‐101 in 2003 and the U.S. rule “Modernization of Oil and Gas Reporting” in 2009 introduced quasi‐identical amendments which effectively tightened the rules governing oil and gas reserve disclosures in both countries. We document significant changes in firms' reporting outcomes when the new regulations are introduced. We also find that the reserve disclosures filed under the new regulations are more closely associated with stock price changes and with decreases in bid‐ask spreads. Our findings are robust to controlling for other confounding factors such as time trends, other information disclosed simultaneously, financial reporting incentives, mispricing, and monitoring efforts.